An environmental scan of one health preparedness and response: the case of the Covid-19 pandemic in Rwanda - Igihozo, Gloria; Henley, Phaedra; Ruckert, Arne; Karangwa, Charles; Habimana, Richard; Manishimwe, Rosine; Ishema, Leandre; Carabin, Hélène; Wiktorowicz, Mary E.; Labonté, Ronald (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Over the past decade, 70% of new and re-emerging infectious disease outbreaks in East Africa have originated from the Congo Basin where Rwanda is located. To respond to these increasing risks of disastrous outbreaks, the government began integrating One Health (OH) into its infectious disease response systems in 2011 to strengthen its preparedness and contain outbreaks. The strong performance of Rwanda in responding to the on-going COVID-19 pandemic makes it an excellent example to understand how the structure and principles of OH were applied during this unprecedented situation. Methods A rapid environmental scan of published and grey literature was conducted between August and December 2020, to assess Rwanda’s OH structure and its response to the COVID-19 pandemic. In total, 132 documents including official government documents, published research, newspaper articles, and policies were analysed using thematic analysis. Results Rwanda’s OH structure consists of multidisciplinary teams from sectors responsible for human, animal, and environmental health. The country has developed OH strategic plans and policies outlining its response to zoonotic infections, integrated OH into university curricula to develop a OH workforce, developed multidisciplinary rapid response teams, and created decentralized laboratories in the animal and human health sectors to strengthen surveillance. To address COVID-19, the country created a preparedness and response plan before its onset, and a multisectoral joint task force was set up to coordinate the response to the pandemic. By leveraging its OH structure, Rwanda was able to rapidly implement a OH-informed response to COVID-19. Conclusion Rwanda’s integration of OH into its response systems to infectious diseases and to COVID-19 demonstrates the importance of applying OH principles into the governance of infectious diseases at all levels. Rwanda exemplifies how preparedness and response to outbreaks and pandemics can be strengthened through multisectoral collaboration mechanisms. We do expect limitations in our findings due to the rapid nature of our environmental scan meant to inform the COVID-19 policy response and would encourage a full situational analysis of OH in Rwanda’s Coronavirus response.